The uniformity and time-invariance of the intra-cluster metal distribution in galaxy clusters from the IllustrisTNG simulations - Vogelsberger, Mark; Springel, Volker; Weinberger, Rainer; Pakmor, Rüdiger; Pillepich, Annalisa; Nelson, Dylan (Arxiv, 2017)
The distribution of metals in the intra-cluster medium encodes important information about the enrichment history and formation of galaxy clusters. Here we explore the metal content of clusters in IllustrisTNG - a new suite of galaxy formation simulations building on the Illustris project. Our cluster sample contains 20 objects in TNG100 - a ~(100 Mpc)^3 volume simulation with 2x1820^3 resolution elements, and 370 objects in TNG300 - a ~(300 Mpc)^3 volume simulation with 2x2500^3 resolution elements. The z=0 metallicity profiles agree with observations, and the enrichment history is consistent with observational data going beyond z~1, showing nearly no metallicity evolution. The abundance profiles vary only minimally within the cluster samples, especially in the outskirts with a relative scatter of ~15%. The average metallicity profile flattens towards the center, where we find a logarithmic slope of -0.1 compared to -0.5 in the outskirts. Cool core clusters have more centrally peaked metallicity profiles (~0.8 solar) compared to non-cool core systems (~0.5 solar), similar to observational trends. Si/Fe and O/Fe radial profiles follow positive gradients. The outer abundance profiles do not evolve below z~2, whereas the inner profiles flatten towards z=0. More than ~80% of the metals in the intra-cluster medium have been accreted from the proto-cluster environment, which has been enriched to ~0.1 solar already at z~2. We conclude that the intra-cluster metal distribution is uniform among our cluster sample, nearly time-invariant in the outskirts for more than 10 Gyr, and forms through a universal enrichment history.